Development of the methods for calculating the main indicators of heat islands in urban areas - Bekirova, Lala; Mammadova, Esmira; Bunyatova, Elvira (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article is dedicated to the methods developed to calculate the main parameters of "heat is lands" that appear in densely built-up urban area. Although remote sensing imaging is ideally used to track and detect frequent land cover changes in urban and surrounding areas as a result of sustainable urbanization and to calculate key parameters of "heat islands" seen in densely populated urban areas, satellite imagery is digitally manually The transformation of a parametric image into a land cover map using existing methods of classification is a long process, and therefore methods are proposed to determine the main indicators of the impact of "heat islands" in urban areas. A modified building density index has been formulated, which is highly informative, involving: (a) the proposed index reaches an extremum when the known building density index BDI and NDVI are equalized, (b) when the specified maximum is reached, it is easy to calculate the LST indicator using the known regression dependences of BDI and NDVI from LST. The method has been developed to calculate the area of "heat islands" on the base of the equivalent radius calculation using the known dependence function of the building density on the distance to the center of the urban area. Our study shows that the distribution of buildings and the slope of the relief affect the surface temperature (LST), in addition, the ratios of different LSTs vary in cities of different sizes, and each city has a temperature difference in LSTs, so the urban heating island To reduce the impact, it is important to identify the characteristics of the thermal environment in cities of different sizes. Urban greening is increasingly valued by cities around the world as an effective measure to reduce the negative effects of the urban heating islands, with different numbers and types of landscape dimensions, different statistical methods used in different surveys, as well as metric scale dependence and contextual differences between cities and we can overcome these challenges by conducting comparative research on time and space using a consistent methodology.

Стаття присвячена розробленим методикам розрахунку основних параметрів "острівців тепла", які виникають у густонаселених міських територіях. Хоча зображення дистанційного зондування ідеально використовується для відстеження та виявлення частих змін ґрунтового покриву в містах та прилеглих районах, у результаті сталої урбанізації та для розрахунку ключових параметрів "острівців тепла", які спостерігаються в густонаселених міських районах, супутникові зображення вручну виконуються в цифровому вигляді. внесення параметричного зображення в карту земного покриву з використанням існуючих методів класифікації є тривалим процесом, тому запропоновано методи визначення основних показників впливу «острівців тепла» в міських районах. Сформульовано модифікований індекс щільності забудови, який є високоінформативним, що включає таке: (a) запропонований індекс досягає екстремуму, коли відомі індекси щільності забудови BDI та NDVI вирівнюються, (b) коли досягається заданий максимум, це надає можливість легко розрахувати показник LST, використовуючи відомі регресійні залежності BDI та NDVI від LST. Розроблено метод розрахунку площі "острівців тепла" на основі розрахунку еквівалентного радіусу з використанням відомої функції залежності щільності забудови від відстані до центру міської території. Наше дослідження показує, що розподіл будівель і нахил рельєфу впливають на температуру поверхні (LST), крім того, співвідношення різних LST різняться в містах різного розміру, і кожне місто має різницю температур в LST, тому є міські острова опалення. Для зменшення впливу важливо визначити характеристики теплового середовища в містах різного розміру. Міста в усьому світі все більше цінують озеленення міста як ефективний захід для зменшення негативного впливу міських островів опалення з різною кількістю та типами ландшафтних розмірів, різними статистичними методами, що використовуються в різних дослідженнях, а також залежністю від метричного масштабу та контексту. розбіжності між містами та нами, може подолати ці проблеми, проводячи порівняльні дослідження часу та простору з використанням послідовної методології.
Розробка методики розрахунку основних показників островів тепла в місці
Keywords: heat islands; urban area; surface temperature; informativeness; method; острівці тепла; міська територія; температура поверхні; інформативність; метод